Tuesday, 12 April 2016

2=1 1=0

Prove 2=1

x = y
x2 = xy
x2 + x2 = x2 + xy
2x2 = x2 + xy
2x2  - 2xy = x2 + xy -2xy
2x2  - 2xy = x2 -xy
2(x2  - xy) = 1(x2 – xy)
2 = 1



Prove 1=0
(x + 1)2  =  x2 + 2x + 1
(x + 1)2 – (2x + 1) = x2
(x + 1)2 – (2x + 1) – x(2x + 1) = x2 – x(2x + 1)
(x + 1)2 – (2x + 1)(x + 1) = x2 – x(2x + 1)
(x + 1)2 – (2x + 1)(x + 1) + (2x + 1)2/4 = x2 – x(2x + 1) + (2x + 1)2/4
[(x + 1) - (2x + 1)/2 ]2 = [x – (2x + 1)/2 ]2
(x + 1) - (2x + 1)/2  = x – (2x + 1)/2
x + 1 = x
1 = 0


Enjoy Videos

No comments:

Post a Comment